Economic Effect of the Coronavirus on the Companies Involved in Car and Automotive Parts Trading, and Manufacture of Tires of Hungary, Including Szabolcs-Szatmár-Bereg County, in Respect of 2020 - Bernadett, Béresné; Maklári, Eszter (International Journal of Engineering and Management Sciences, 2022)
In Hungary the wake of the first wave of the Covid-19 epidemic (March 2020), caused a decline in demand for goods and services in most sectors. There were sectors (accommodation services, art, recreation, etc.), which were economically severely burdened by the imposition of restrictive measures, and there were some (financial services, communication), which experienced the change positively. In our research, our goal was to assess the changes caused by the Covid-19 epidemic in the property, financial and profitability situation of the companies involved in car and automotive parts trading, and tire manufacturing, in Hungary, and within the country, in Szabolcs-Szatmár-Bereg county. We established three hypotheses: (1) As a result of the spread of coronavirus epidemic, in Hungary and in Szabolcs-Szatmár-Bereg county as well, the profitability of companies of NAICS codes 441 (car and automotive parts trading) and 4231 (wholesale of road vehicles and parts), decreased. (2) The outbreak of the epidemic had a negative impact on the liquidity of companies established in Hungary, including Szabolcs- Szatmár-Bereg county. (3) As a result of the Covid-19 epidemic, the resource structure of Szabolcs-Szatmár-Bereg county companies, analysed in the framework of research work, transformed. To prove or disprove these, secondary research was used. Finally, we put forward conclusions and proposals for the management of the companies active in this industry.